ARI updates 2019 - UiTM, Accounting Research Institute (Accounting Research Institute (ARI), 2019)
Accounting Research Institute (ARI) of UiTM was first formed in 2002 as a special interest group whereas illustrate a history victorious history despite its relative youth. Since then, ARI had gone through a complete evolutionary cycle which includes of first being a special interest group (SIG), then as a research centre and finally as a research institute.